Synthesis of polyhydroxylated conidine alkaloid as a conformationally restricted azasugar - Pal, Sujit; Dumbre, Shrinivas G. (Synlett, 2016)
A conformationally restricted polyhydroxylated 1-azabicyclo[4.2.0]octane core has been synthesized in search for a potent selective glycosidase inhibitor. The key feature of the synthesis involves the high stereoselective photoelectron-transfer-promoted cyclization of the strained alpha-trimethylsilylmethylazetidine moiety to the tethered pi functionality.